Love as Care: Ibn ‘Arabi’s Ethics of Love and Its Resonances with the Ethics of Care - m minanur rohman (Yayasan Azhar Amanaa Yogyakarta, 2026)
This article argues that Islam ought to be understood as a love-oriented religion rather than one defined solely by law and regulation. Challenging the reductive characterization of Islam as a purely nomos-oriented tradition, the article examines Ibn ʻArabi’s ethics of love through the lens of the ethics of care, employing library research with thematic-comparative content analysis as its methodological framework. Drawing on both primary and secondary sources, the study identifies five key variables within Ibn ʻArabi’s love ethics: (1) the undefinability of love, (2) insān kāmil, (3) jamāl-Ihṣān, (4) jamāl and jalāl, and (5) tajallī. Each variable is analyzed in comparative dialogue with the care-ethical thought of Iris Murdoch, Carol Gilligan, Emmanuel Lévinas, and Robert Spaemann, revealing substantive resonances between Akbarian mystical ethics and contemporary Western moral philosophy. The findings suggest that Ibn ʻArabi’s love ethics constitutes a viable corrective framework for contemporary religious discourse, pointing beyond sectarian fanaticism toward a spirituality grounded in care, beauty, and universal compassion.